Insulinoma Presenting as a Complex Partial Seizure: Still a Possible Misleading Factor - Qi, Ziyou; Li, Daojing; Ma, Jinfeng; Xu, Peng; Hao, Yongnan; Zhang, Aimei (Frontiers in Neuroscience, 2020)
Delayed diagnosis of insulinoma remains an intractable clinical challenge because the symptoms are in most cases misattributed to other disorders. In this study, a 64-year-old man presented with intermittent seizure episodes after being misdiagnosed with epilepsy and receiving anti-epileptic drugs for 4 years. During this period, the patient continued to suffer from repeated seizures. Starvation test, pancreatic enhancement CT, MRI scan and pathological examination clinically diagnosed insulinoma and the symptoms improved following surgical removal of the tumor. The appearance of unusual manifestations and insulinoma imaging makes it difficult to accurately diagnose the condition. This case emphasizes the need for careful reassessment of all atypical and refractory seizures.